Pembaruan Hukum Keluarga di Yaman - Roby; Syarifudin; Ali Murtadho (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the transformation of family law in Yemen and the Family Law in Yemen. The research method used is library research. The transformation of family law in Yemen reflects a long journey influenced by social, political, and religious dynamics. As a country that adheres to Islamic law, Yemen adopts a family law system influenced by traditional Islamic schools of thought. Yemeni family law has undergone reforms, starting with the implementation of the Qanun al-Usrah in 1974 in South Yemen, leading to the enactment of Law No. 27 of 1998 after the unification of North and South Yemen. These reforms aim to adapt family law to modern social and political needs. However, despite progress in legal reforms, significant challenges remain in the implementation of family law, such as child marriage and child custody after divorce, which continue to face substantial barriers. This article examines the history, challenges, and transformation of family law in Yemen, as well as the need for further reforms to achieve justice and equality in family law.